Multi-Interpreter Systems - Derrett, Nigel; Manthey, Michael J. (DAIMI Report Series, 1976)
This paper is concerned with systems to support high-level-language- oriented interpreted machines. Certain requirements for such a system are presented and some of the problems which arise are discussed.